TEKNIK BUDIDAYA DAN PASCA PANEN IKAN NILA SALIN BAGI MASYARAKAT PEMBUDIDAYA DI DESA SEDARI, KECAMATAN CIBUAYA, KABUPATEN KARAWANG - Pramono Adi, Catur (JURNAL KASTARA, 2022)
Cibuaya District, Karawang Regency, was designated as a Fish Cultivation Village in 2022. Then to increase awareness of coastal communities, especially fish cultivators, on the importance of the community's role for the welfare of family members from fish farming businesses. This activity is a form of community service from the Fishery Product Processing Engineering Study Program at the KP Karawang Polytechnic as a form of implementing the third dharma of the Tridharma of Higher Education. Activities and continuity of community service are actually very important both for university managers as well as for the existence of these universities in the community. Community service with the topic of "Cultivation and Post-Harvest Techniques Tilapia" was held in Sedari Village, Cibuaya District, Karawang Regency, West Java, attended by community members, especially cultivators, Sedari village officials, Fisheries Extension Officers, and community leaders. Sedari Village The community service method is carried out by direct counseling in the Sedari village meeting room. The community service program has been carried out well with the support of the Sedari village, extension workers, and the Karawang Regency Marine and Fisheries Service.